2021
DOI: 10.17712/nsj.2021.2.20200148
|View full text |Cite
|
Sign up to set email alerts
|

Low versus standard dose intravenous alteplase in the treatment of acute ischemic stroke in Egyptian patients

Abstract: ‫يوم‬ 90 ‫في‬ ‫إيجابية‬ ‫(العدد=2)‬ 5% ‫ا‬ ً ‫يوم‬ 90 ‫ملدة‬ ‫الوفيات‬ ‫معدل‬ ‫كان‬ .)p=0.631( ‫الثانية‬ ‫الثانية‬ ‫املجموعة‬ ‫في‬ ‫(العدد=1)‬ 2.5% ‫مقابل‬ ‫األولى‬ ‫املجموعة‬ ‫في‬ ‫في‬ ‫مرضى‬ 3 ‫في‬ ‫اجلمجمة‬ ‫داخل‬ ‫نزيف‬ ‫أعراض‬ ‫وحظ‬ ٌ ‫ل‬ .)p=0.556( .)p=0.077( ‫األولى‬ ‫املجموعة‬ ‫في‬ ‫وصفر‬ ‫الثانية‬ ‫املجموعة‬ ‫ا‬ ً ‫عملي‬ ً ‫بديال‬ ‫تكون‬ ‫أن‬ ‫ميكن‬ ‫التيبالز‬ ‫من‬ ‫منخفضة‬ ‫جرعة‬ ‫اخلالصة:‬ ‫فترة‬ ‫في‬ ‫خاصة‬ ‫احلادة‬ ‫الدماغية‬ ‫بالسكتة‬ ‫املصابني‬ ‫املصريني‬ ‫للسكان‬ ‫ساعات.‬ 4.5 ‫إلى‬ 3 ‫من‬ ‫تترا… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Finally, 18 studies were included in the qualitative synthesis ( 7 11 , 19 , 20 , 30 40 ). The doses of three studies ( 30 , 34 , 39 ) did not meet the design of the present study and one study ( 40 ) without specific data was excluded from the final quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 18 studies were included in the qualitative synthesis ( 7 11 , 19 , 20 , 30 40 ). The doses of three studies ( 30 , 34 , 39 ) did not meet the design of the present study and one study ( 40 ) without specific data was excluded from the final quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The doses of three studies ( 30 , 34 , 39 ) did not meet the design of the present study and one study ( 40 ) without specific data was excluded from the final quantitative analysis. Fourteen studies were included in the quantitative synthesis ( 7 11 , 19 , 20 , 31 33 , 35 38 ). Table 1 summarizes the characteristics of the 14 included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources: [13][14][15][16][17][18][19][20][21][22]24,[26][27] Mortality: in the present meta-analysis, a total of 15 studies were included that compared the risk of mortality between low-dose and standard-dose alteplase. The incidence of mortality was lower in the lowdose group (9.72%) compared to the high-dose group (11.24%; RR: 0.93, 95% CI: 0.83-1.04), as shown in Figure 3.…”
Section: Figure 2: Forest Plot Comparing Favorable Outcome Between Lo...mentioning
confidence: 99%
“…A 2017 meta-analysis involving 12 studies found no significant difference between low dose and standard dose of r-tPA in terms of mortality and favorable outcomes [12]. Since this meta-analysis, certain new studies have been conducted to compare the efficacy and safety of low doses and standard doses, including non-randomized studies [13] and retrospective cohorts conducted in different regions of the world [14][15][16].…”
Section: Introductionmentioning
confidence: 99%